The culture of Dunaliella salina and the production of Î²-carotene in tannery effluents,The culture of Dunaliella salina and the production of [beta]-carotene in tannery effluents - Laubscher, Richard Keith (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1992)
The problems of waste disposal in the tanning industry are unique in that the effluents are highly saline, have a high organic loading and contain heavy metals. Methods are available for the safe treatment and disposal of the latter two components, but the saline component requires the expensive outlay of evaporation ponds. This study has identified a possible use for the saline effluents, turning a problematic waste product into a potentially valuable by-product. A range of tannery effluents were identified and tested for their suitability for the mass cultivation of Dunaliella salina (bardawil strain). The bardawil strain was preferred over a local isolate because of its higher production of Î²-carotene. Ponded tannery effluents and combined processes effluent proved unsuitable for realistic propagation of the alga. Anaerobic digestion of combined processes effluent did not improve its suitability significantly. Anaerobic digestion of hide-soak effluent may remove persistent antimicrobial agents which influence algal growth, but its contribution to enhancing algal growth is equivocal. Undigested hide-soak effluent lacking in persistent antimicrobial agents was found to be an ideal culture medium, as no additional nutrients needed to be added. Significantly higher biomass was obtained in this effluent compared to chemically defined media. Induction of Î²-carotene was achieved in nitrogen-deficient defined media after culture in tannery effluent. This suggests that a two-stage system using hide-soak effluent for cell propagation and nitrogen deficient media for Î²-carotene induction, could be possible for the mass cultivation of D. salina for Î²-carotene production.
Keywords: Dunaliella; Carotenes; Tanneries -- Waste disposal; Recycling (Waste, etc.)